Design and Implementation Of Restful Api Using Oauth 2.0 Authentication In Laravel Framework On Marketplace (Case Study: CV. Marvelindo Utama) - Nugraha, Varrel Bramasta; Usman, Muhammad Lulu Latif (Yayasan Kita Menulis, 2024)
CV Marvelindo Utama is an electronics company that sells data packages and other internet-related products, with distribution warehouses and branch outlets across various regions. The company's challenge lies in its manual marketing through WhatsApp. This research aims to address this issue by designing a Supply Chain Management system for the marketplace using REST API and Oauth 2.0 authentication to ensure data security. The Extreme Programming (XP) application development method is used to expedite the development process. This research is expected to help CV Marvelindo Utama face modern technological challenges and improve operational efficiency. Testing results using blackbox and unit testing indicate that the system meets the requirements, with blackbox testing achieving a 100% success rate and unit testing yielding positive results.